2012
DOI: 10.1371/journal.pone.0038131
|View full text |Cite
|
Sign up to set email alerts
|

Variance and Autocorrelation of the Spontaneous Slow Brain Activity

Abstract: Slow (<0.1 Hz) oscillatory activity in the human brain, as measured by functional magnetic imaging, has been used to identify neural networks and their dysfunction in specific brain diseases. Its intrinsic properties may also be useful to investigate brain functions. We investigated the two functional maps: variance and first order autocorrelation coefficient (r 1). These two maps had distinct spatial distributions and the values were significantly different among the subdivisions of the precuneus and posterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…where r jk is the correlation between original overt speech and reconstruction, r jh is the correlation between original overt speech and baseline reconstruction and r kh is the correlation between overt speech reconstruction and baseline reconstruction; df = n − 3 is the effective sample size (Kaneoke et al, 2012) and where…”
Section: Methodsmentioning
confidence: 99%
“…where r jk is the correlation between original overt speech and reconstruction, r jh is the correlation between original overt speech and baseline reconstruction and r kh is the correlation between overt speech reconstruction and baseline reconstruction; df = n − 3 is the effective sample size (Kaneoke et al, 2012) and where…”
Section: Methodsmentioning
confidence: 99%
“…Various brain networks relevant to specific functions and diseases have been identified [13][20]. Electrophysiological studies have presented evidence of a modified CNS network in tinnitus subjects [21], [22].…”
Section: Introductionmentioning
confidence: 99%
“…Because time series data is not random, the effective sample size of independent measurements across time must be estimated in order to calculate the statistical significance of FC [29]. The effective sample size can be estimated using the autocorrelation coefficient (AC) in the two regions as discussed in our previous study [20]. AC has physiological relevance [20], with low autocorrelation values distributed around the caudal brain regions and high values observed in the default mode network (DMN) regions, defined as “ a specific, anatomically defined brain system preferentially active when individuals are not focused on the external environment” [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maxim et al modeled the noise of rsfMRI data with a fractional Gaussian noise model and demonstrated that variance of rsfMRI was higher in ventricles and the rim of cortices and patients with Alzheimer’s disease had higher variance in places near the ventricles and sulcal CSF [29]. Kaneoke et al [21] showed higher variance also in regions near brain ventricles and CSF but lower variance in many other places including temporal lobes, striatum, insula, visual cortex, and prefrontal cortex. No one has yet paid attention to the higher-order TTFs.…”
Section: Introductionmentioning
confidence: 99%